A putative association of interleukin‐10 promoter polymorphisms with cardiovascular disease. Issue 7 (5th May 2017) - Tabrez, Shams; Ali, Murtaza; Jabir, Nasimudeen R.; Firoz, Chelapram K.; Ashraf, Ghulam Md.; Hindawi, Salwa; Damanhouri, Ghazi A.; Nabil Alama, Mohammed
Abstract: Interleukin‐10 (IL‐10) is an anti inflammatory cytokine involved in the ongoing coronary inflammation and related patho‐physiological processes. The piece of work presented herein is aimed at investigating possible association of polymorphisms in IL‐10 promoter with Saudi cardiovascular disease (CVD) patients. The study included 80 confirmed CVD patients with diabetes and 75 healthy control individuals both men and women. Concentration of IL‐10 in the serum samples were measured by ELISA method. For single nucleotide polymorphism (SNP) analysis, Sanger method of DNA sequencing was followed. The IL‐10 level was found to be significantly elevated in CVD patients ( P < 0.001) and its associated complications viz. ST‐elevation myocardial infarction [STEMI] ( P <0.01), non ST‐elevation myocardial infarction [NSTEMI] ( P < 0.05), and unstable angina [UA] ( P < 0.001). We also observed a significant association between polymorphisms in IL‐10 promoter at −1082 and −819 locus with Saudi CVD patients. Moreover, at −1082 A/G locus, AA haplotype was found to be less frequent in the CVD patients compared with control individuals. On the other hand, highly significant rise in heterozygous (A/G genotype) condition was observed in patient samples compared with control ones ( P < 0.001). Similarly, the genotypic frequencies at −819 C/T locus were also found to be significantly associated ( P < 0.001) with CVD patients compared with control individuals. Our study provides the status of polymorphism in IL‐10 promoter and its association with CVD risk in Saudi population. As per our information, ours is the first article that shows the genetic diversity in IL‐10 promoters and its level in the Saudi CVD patients. © 2017 IUBMB Life, 69(7):522–527, 2017